Solusi Mengatasi Kejenuhan dalam Menjalankan Praktik bagi Pekerja Sosial - Nur Afni; Aziz Muslim (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Boredom at work is something that cannot be denied because it is common and we often get it in the world of work, so that boredom can interfere with concentration at work, especially in social work practices. therefore overcoming this saturation needs to be done so that unwanted things don't happen at work so that this saturation point can be resolved properly. This research study was conducted in Aceh. The method used in this study is descriptive qualitative, in which researchers collect data by conducting interviews with informants. The conclusion that the writer gets is that social workers who have managed to get through this saturation, by carrying out the practical methods applied include: (a) Self Healing (b) Self Reward (c) Quality time, (d) Self care, (e) Sharing Sesion.